Case Report: Diagnostic Dilemma between Atypical Meningioma and Glioblastoma-our Observation - Akhlaque Hossain Khan; Mehedi Hasan Munna; Muhammad Saiful Islam; Sumaiya Rahman; Tofayel Ahmed; Ripon, Jalal Ahmed; Islam, Rahatul; Islam, Ariful; Mamun, Abdullah Al; Dorji, Tandin Wangyel; et al. (Bangladesh Journal of Neurosurgery, 2024)
Both meningioma and glioblastoma are very common intra-cranial neoplasm. Typically both have distinguishing clinical and radiological features which aid in diagnosis and thus pre-operative preparation, planning, counseling the patient etc. But dilemma may often arise in case of non-grade-I meningioma making confusion in favor of higher grade astrocytoma (glioblastoma). In that case total per-operative picture, surgical approach, post- operative managements, and disease prognosis will be altered. We faced such kind of confusion in a case so reported here. Bang. J Neurosurgery 2024; 13(2): 157-161